2001
DOI: 10.1104/pp.125.1.406
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Trait Loci for Component Physiological Traits Determining Salt Tolerance in Rice

Abstract: Rice (Oryza sativa) is sensitive to salinity, which affects one-fifth of irrigated land worldwide. Reducing sodium and chloride uptake into rice while maintaining potassium uptake are characteristics that would aid growth under saline conditions. We describe genetic determinants of the net quantity of ions transported to the shoot, clearly distinguishing between quantitative trait loci (QTL) for the quantity of ions in a shoot and for those that affect the concentration of an ion in the shoot. The latter coinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

15
211
3
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 304 publications
(235 citation statements)
references
References 65 publications
15
211
3
1
Order By: Relevance
“…These results indicate that the salt-tolerance of SM61 was governed by a single dominant gene. These results differ from those obtained in some traditional indica salt-tolerant varieties, such as Pokkali, Nona Bokra, and Kararata, in which inheritance of salt-tolerance is known to be governed by polygenes (Zhang et al, 1995;Lin et al, 1998;Gong et al, 1999;Prasad et al, 2000;Koyama et al, 2001;Lin et al, 2004). This is the fi rst report that in F 1 and F 2 salt-tolerant rice plants, the salt-tolerance is governed by a single dominant gene.…”
Section: Discussioncontrasting
confidence: 55%
See 4 more Smart Citations
“…These results indicate that the salt-tolerance of SM61 was governed by a single dominant gene. These results differ from those obtained in some traditional indica salt-tolerant varieties, such as Pokkali, Nona Bokra, and Kararata, in which inheritance of salt-tolerance is known to be governed by polygenes (Zhang et al, 1995;Lin et al, 1998;Gong et al, 1999;Prasad et al, 2000;Koyama et al, 2001;Lin et al, 2004). This is the fi rst report that in F 1 and F 2 salt-tolerant rice plants, the salt-tolerance is governed by a single dominant gene.…”
Section: Discussioncontrasting
confidence: 55%
“…Thirtyone F 3 lines derived from the F 2 salt-tolerant plants were used to evaluate the genotypes of F 2 plants. We found that the SM61 mutated salt-tolerance gene, ST8, is located on chromosome 8, different from those previous QTL regions previously discovered on chromosome 1, 3, 4, 5, 6, 7, 9, 10 and 12 (Zhang et al, 1995;Lin et al, 1998;Gong et al, 1999;Prasad et al, 2000;Koyama et al, 2001;Lin et al, 2004;Ren et al, 2005;Lee et al, 2007;Sabouri and Sabouri, 2008). By applying MAS techniques to the gene we have identified as responsible for conferring salttolerance, the results of our study could be used to improve salt tolerance of japonica scented rice.…”
Section: Discussioncontrasting
confidence: 51%
See 3 more Smart Citations